Housing facilities for the displaced Remontados cultural identity preservation amidst environmental change - Sy-changco, Ma. Celina A. (Quezon City College of Architecture, University of the Philippines Diliman, 2008)
The study is on the preservation of cultural identity of the displaced Remontado amidst environmental change.By analyzing the relationship between culture and environment, a set of housing facilities guidelines was developed to ensure that the relocation site contains the appropriate environment to sustain their ways of life.
Vita.
Thesis (Master of Architecture)--University of the Philippines, Diliman.
Keywords: Remontado tribe -- Housing; Dwellings